Reconstructing Arabic Speaking Development: The Hidden Role of Communicative Pedagogy and Self-Efficacy in Undergraduate Learners - Salsa Hauna Ajidin; Yanda Rismawati; Asep Ajidin; Arya Yudiawan; Muhammad Alief (At Turots: Jurnal Pendidikan Islam, 2026)
Arabic language learning in higher education is still largely dominated by structural approaches, which often limit students’ opportunities to develop speaking proficiency. This study aims to reconstruct the development of Arabic speaking skills (Mahārat al-Kalām) by examining the interaction between communicative pedagogy and learners’ self-efficacy in undergraduate contexts. Using an archival qualitative research design, the study analyzes lesson plans (RPS), assessment rubrics, classroom video recordings, and interaction transcripts from an al-Kalām course. Data were examined through Conversation Analysis, Thematic Analysis, and Communicative Approach Analysis to capture interactional patterns, psychological dimensions, and pedagogical alignment. The findings show that communicative activities such as intonation imitation, object description, thematic dialogue, project-based tasks, and interaction with native speakers stimulate spontaneous oral production and foster meaning negotiation. Students demonstrated increased initiative, self-repair, and sustained turn-taking, indicating the development of communicative competence. Thematic analysis further reveals that repeated communicative experiences strengthen students’ self-efficacy through mastery experiences, social support, and a supportive classroom environment. The study concludes that Arabic speaking development does not emerge spontaneously but is systematically constructed through the integration of communicative instructional design and learners’ psychological readiness. These findings highlight the importance of aligning pedagogical planning and affective support to enhance speaking proficiency in higher education